The use of lysosomal enzymuria in the early detection and monitoring of the progression of diabetic nephropathy - Gatsing, Donatien (Springer India, 2006)
Recent acquisitions on the early detection and monitoring of the progression of diabetic complications (nephropathy) using the techniques of enzymology (lysosomal enzymes) are reviewed. it appears that the kidney is the principal source of urinary lysosomal enzymes. Urinary samples for lysosomal enzyme determination can be either 24-hour or spot-collection. The use of synthetic substrates (4-methylumbelliferyl substrates) provides an easy, inexpensive, sensitive and highly reproducible method of lysosomal enzyme assay. It is recommended that more than one enzyme be assayed in the process. The use of fractional enzyme excretion (FEE) ratios is further recommended. The urinary lysosomal glycosidases investigated and found to be of particular diagnostic value in the early detection of diabetic nephropathy include N-acetyl-β-D-glucosaminidase (β-hexosaminidase, NAG), β-glucuronidase and β-galactosidase, with NAG being the most useful indicator. Urinary NAG can be used in monitoring the progression of diabetic nephropathy. The fluorimetric assay of lysosomal glycosidases is particuarly recommended in developing countries since it is simple, sensitive and inexpensive.